Peranan Bagian Hukum Sekretariat Daerah Kota Bandar Lampung Dalam Operasi Yustisi Penanganan Covid-19 - Dery Hendryan; Muhammad Rusjana; Yudi Yusnandi (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
One of the main duties and functions of the Legal Department as regulated by the Mayor of Bandar Lampung No. 38 of 2021 Article 9 paragraph (1). There is Regional Regulation No. 1 of 2018. During the Covid-19 pandemic, the government issued Mayor's regulation Bandar Lampung city No. 18 of 2020 and No. 25 of 2020. This regulation forms the juridical basis and technical guidelines for judicial operations in handling Covid-19. The problem in this research is, what is the role of the Legal Department of the Bandar Lampung City Regional Secretariat in the justice operations in handling Covid-19? And what are the supporting and inhibiting factors in carrying out the justice operation? The research method is a normative juridical approach and an empirical juridical approach using secondary data and primary data. The results of the study, that the role of the Legal Department in the efforts of the Judicial Operations for Handling Covid-19 for Enforcement of Legislation, are in the form of: (1) not optimal due to the absence of the main tasks and functions of the Legal Section in Regional Regulation No. 1 of 2018, Mayor Regulation No. 18 of 2020 and Mayor Regulation No. 25 of 2020, (2) coaching (socialization/ education), written warnings 1, 2 and 3, controlling and sealing, (3) does not have a deterrent effect on residents and business actors because of light sanctions. Supporting factors for the Judicial Operations handling of Covid-19, namely: (1) support from the Mayor according to the vision and mission for Bandar Lampung, Healthy, Smart, Faithful, Cultured, Comfortable, Superior, Competitive, Based on the Economy for the Prosperity of the People, (2) coordination between agencies related very well and (3) the actions of the PPNS/Justisi Team were accompanied by the police as the PPNS Supervisory Board. The inhibiting factors are: (1) lack of facilities and infrastructure, (2) limited number of PPNS and (3) the Regional Regulation on Covid-19 does not yet exist, as a result of which sanctions and fines cannot be applied.